Testing the effectiveness of an algorithm for suppressing self-excited vibrations during intensive braking of a vehicle - A. V. Klimov (Вестник СибАДИ, 2024)
Introduction. When the vehicle slows down, particularly on slippery surfaces, stability of the electromechanical drive system movement can be reduced, which is accompanied by high self-excited vibrations. These vibrations occur when the sliding speed increases and the friction force decreases. At the same time, the dynamic load on the drive system increases sharply, which can lead to its failure. Thus, the development of methods for suppressing self-excited vibrations is an urgent task.The purpose of the study is to test the operability and effectiveness of the method for suppressing self-excited vibrations in the electromechanical wheel drive system during braking with the use of methods of field experiments.Materials and methods. The study of the efficiency and effectiveness of the algorithm was based on field experiments.Results. Based on field experiment method, the efficiency and effectiveness of the algorithm for suppressing self-excited vibrations during deceleration has been determined, which allows for six-fold reduction in maximum amplitudes and 3-3,5-fold reduction in averaged amplitudes, while excluding changes in the moment sign during vehicle intense deceleration.Conclusion. The algorithm of suppressing self-excited vibrations can be recommended for application in developing vehicle deceleration control systems